The treasure of the Sierra Madre [videorecording (DVD)] - Huston, John, 1906-1987; Bogart, Humphrey, 1899-1957; Huston, Walter, 1884-1950; Holt, Tim, 1918-1973; Traven, B. (2003)
Two down-and-out Americans in Mexico meet a grizzled old prospector who piques their interest with stories of his gold-hunting experiences. The Americans gather a stake and set off with the old prospector in search of fortune.